The youth political participation in the European Union - Morchón, David Redoli (2006)
All social agents share the younger generations’ actual success or failure to integrate and develop within society. In order to achieve their effective citizenship, youths require institutional structures that may allow them to participate actively in public events and become satisfactorily self-supporting. Since youth is the stage in life when citizenship is shaped, all EU’s governmental bodies, member states and regional administrations are responsible for implementing the necessary resources to enhance youths’ active participation. Younger cohorts in Europe are likely to lead a new definition of our current social structures. In this sense, the European youth associations’ movement - given its extension – is one of the key agents to be considered. The design and implementation of current and future youth services across Europe will have to take into account such platforms as the European Youth Forum (YFJ), an international youth organisation catering for the needs of young people. The European Youth Forum (YFJ), set up in Brussels in 1996, is a democratic platform advocating for the interests of more than 10 million young Europeans and co-ordinating 91 member organisations, including national youth councils and youth NGOs across Europe. This text aims to explain the YFJ’s internal structure and the range of services it provides to European youth organisations. Moreover, it also aims to highlight the importance of the YFJ’s actions regarding the European youths involvement in the current socio-demographic context. Key words: Youths; Youth services; European Youth Forum (YFJ); Youth emancipation; International co-operation; European Union.